2001
DOI: 10.1517/14656566.2.7.1167
|View full text |Cite
|
Sign up to set email alerts
|

Topical tacrolimus for the treatment of inflammatory skin diseases

Abstract: Chronic inflammatory skin disorders, such as atopic eczema, can cause considerable impairment of life quality. Their treatment is mainly driven by systemic or topical glucocorticosteroids which have the risk of many side effects. Recently, immunosuppressive macrolides which act via the inhibition of cytokine expression in T-lymphocytes have been shown to exert good therapeutic potency in inflammatory skin disorders. Cyclosporin, widely used in transplantation medicine, is also effective in psoriasis and atopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
6

Year Published

2003
2003
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 57 publications
2
34
0
6
Order By: Relevance
“…Topical application of FK506 ointment exerts good therapeutic efficacy in atopic eczema [9]. FK506 ointment penetrates through skin [10], and clinical studies have shown that FK506 reduces cytokine production and infiltration of T helper (Th) cells in the skin of AD patients [11]. Treatment with FK506 ointment in the conventional NC/Nga model also produces a decreased level of clinical signs and the reduction of Th2 cytokines in the skin [12].…”
Section: Introductionmentioning
confidence: 99%
“…Topical application of FK506 ointment exerts good therapeutic efficacy in atopic eczema [9]. FK506 ointment penetrates through skin [10], and clinical studies have shown that FK506 reduces cytokine production and infiltration of T helper (Th) cells in the skin of AD patients [11]. Treatment with FK506 ointment in the conventional NC/Nga model also produces a decreased level of clinical signs and the reduction of Th2 cytokines in the skin [12].…”
Section: Introductionmentioning
confidence: 99%
“…Es bewirkt über eine Hemmung der Calcium/Calmodulin-abhängige Phosphatase Calcineurin eine Reduktion der Zytokinausschüttung (IFN-γ, IL-2, IL-4, IL-10) und damit eine Blockade der T-Zellaktivität [13]. Wäh-rend Ciclosporin die Haut nur schlecht durchdringt, weisen topisches Pimecrolimus und Tacrolimus eine gute Penetrationsfähigkeit auf [2,4]. Pimecrolimus ist in Deutschland zur Behandlung der atopischen Dermatitis ab dem 2.…”
Section: Diskussionunclassified
“…Calcineurin-Inhibitoren), was zur Blockade der T-Zell-Aktivierung und der Zytokinausschüttung führt. Calcineurin-Inhibitoren hemmen insbesondere die Produktion der Th 1 -Zytokine IFN-γ, IL-2 sowie der Th 2 -Zytokine IL-4 und IL-10 [3]. Während Ciclosporin die Haut nur schlecht penetriert,wurden topisches Tacrolimus und Pimecrolimus vor kurzem in die dermatologische Therapie eingeführt.…”
Section: Immune-response-modulatorenunclassified
“…Tacrolimus ist lipophil und hemmt den "second messenger" Calcineurin, was zur Hemmung der Transkription proinflammatorischer Zytokine wie Interleukin-2 und Interferon-γ führt [3].Die Klasse der Calcineurin-Inhibitoren reduziert die Antigenprozessierung und die T-Zell-Aktivierung. Daneben hat Tacrolimus hemmende Wirkung auf Mastzellen und basophile Granulozyten und die Zytokine IL-3, IL-8, IL-13, and GM-CSF.…”
Section: Tacrolimusunclassified